PENGEMBANGAN BUKU â€œKISANAKâ€ SEBAGAI MEDIA PENDIDIKAN KARAKTER UNTUK SISWA SEKOLAH DASAR - Maria Ulfa Julistiyana; Sripit Widiastuti (Universitas Sarjanawiyata Tamansiswa, 2020)
Character education must be instilled continuously. The efforts to infuse character education in an educational environment could be made through the learning of drama. The teaching of drama conducted in the Undergraduate Study Program of Elementary School Teacher Education at Blitar Islamic University had not used drama scripts originating from the local wisdom around of Blitar; accordingly, the efforts to instill character through learning could not be maximally carried out. These efforts aimed to improve the quality of drama art learning through the development of the teaching materials based on the local wisdom in Blitar City and its surroundings. The local wisdom, in this case, encompassed both oral and non-verbal folklore around the City of Blitar. This research was a type of design research. The purpose of this research was to develop and provide product results that contributed positively to solve problems in the world of education. The product of this research was a collection of drama scripts originating from local wisdom around Blitar City. This study used a development model adopted from the Plomp research model